The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1551-2916.2008.02920.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sr/Ti Stoichiometry on the Densification Behavior of Strontium Titanate

Abstract: In order to control the preparation of strontium titanate with a well‐defined Sr/Ti stoichiometry produced by the mixed oxide route, dilatometric experiments have been conducted for compositions with Sr/Ti ratios ranging from 0.996 to 1.005. A significant change in sintering behavior has been detected going from a titania rich to a strontia rich composition. Combining observations of the microstructural evolution during different stages of sintering with results on defect chemistry from the literature makes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 24 publications
(34 reference statements)
3
35
0
Order By: Relevance
“…It was found that ASR LF +HF for both YS98TO and YS88TO samples is comparable (around 350 Ω cm). Thus, the influence of Sr nonstoichiometry can not be identified by the impedance spectroscopy measurements of donordoped SrTiO 3 . That leads to a conclusion that a relationship between microstructure of Y-doped SrTiO 3 and its electrical properties cannot be seen on impedance spectra.…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that ASR LF +HF for both YS98TO and YS88TO samples is comparable (around 350 Ω cm). Thus, the influence of Sr nonstoichiometry can not be identified by the impedance spectroscopy measurements of donordoped SrTiO 3 . That leads to a conclusion that a relationship between microstructure of Y-doped SrTiO 3 and its electrical properties cannot be seen on impedance spectra.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…One of the most widely used representatives of perovskite materials is strontium titanate (SrTiO 3 ). It has been reported in the literature that it is one of the most promising candidates for anode and cathode materials for Solid Oxide Fuel Cells, because of catalytic and conductivity performance [3,20]. However, in a pure form strontium titanate is a dielectric material, so it requires some modifications.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations